Reduced UPF1 levels in senescence impair nonsense-mediated mRNA decay - Dahyeon Koh; Yebin Lee; Kyuchan Kim; Hyeong Bin Jeon; Chaehwan Oh; Sangik Hwang; Minjung Lim; Kwang-Pyo Lee; Yeonkyoung Park; Yong Ryoul Yang; Yoon Ki Kim; Donghwan Shim; et al. (Communications Biology)
Abstract Cells regulate gene expression through various RNA regulatory mechanisms, and this regulation often becomes less efficient with age, contributing to accelerated aging and various age-related diseases. Nonsense-mediated mRNA decay (NMD), a well-characterized RNA surveillance mechanism, degrades aberrant mRNAs with premature termination codons (PTCs) to prevent the synthesis of truncated proteins. While the role of NMD in cancer and developmental and genetic diseases is well documented, its implications in human aging remain largely unexplored. This study reveals a significant decline in the levels of the protein UPF1, a key player in NMD, during cellular senescence. Additionally, NMD substrates accumulate in senescent cells, along with decreased levels of cap-binding protein 80/20 (CBP80/20)-dependent translation (CT) factors and reduced binding to active polysomes, indicating reduced efficiency of NMD. Moreover, knockdown of UPF1 in proliferating WI-38 cells induces senescence, as evidenced by increased senescence-associated β-galactosidase activity, alterations in senescence-associated molecular markers, increased endogenous γ-H2AX levels, and reduced cell proliferation. These findings suggest that the decline in UPF1 levels during cellular senescence accelerates the senescent phenotype by impairing NMD activity and the consequent accumulation of abnormal mRNA.